Reliability and validity of the Dental Indifference Scale in a population of 18-year-olds in Norway - Skaret E, Raadal M, Kvale G, Berg E (Blackwell Synergy, 2000)
The aims of this study were to estimate the reliability and validity of the Dental Indifference Scale (DIS) (Nuttall, 1996) in a population of 18- yr-olds in Norway. Methods: The DIS-scale was mailed to a sample of 1119 18-yrolds in two Norwegian counties. Nearly 87% completed the questionnaire and consented to the collection of data from their dental records. Ten percent of the sample, drawn at random, was asked to complete the questionnaire a second time, after a time delay of 15 weeks (response rate 83%). The reliability estimation of the sum-scores of DIS was based on Pearson’s correlation between test-retest scores and internal consistency (Cronbach’s alpha). The frequency of missed appointments from age 12, recorded in the dental treatment records, was used as the validating criterion.